Cooperation, discounting, and the effects of delayed costs and benefits - Felix Kölle; Thomas Lauer (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2018)
Numerous studies have investigated how people resolve intertemporal trade-offs in individual decision making, but little is known about how the timing of costs and benefits affects behavior in strategic decision situations. Here, we experimentally study how delayed costs and/or benefits affect cooperation in a social dilemma situation. We find that cooperation is substantially reduced (increased) when only the benefits (costs) of cooperation are shifted towards the future. We show that the change in contributions can be explained by (i ) a shift in the beliefs about others' cooperativeness, (ii ) a shift in subjects' willingness to conditionally cooperate, and (iii ) a subject's degree of impatience. We further demonstrate that the amount of economic incentives needed to close the cooperation gap are substantial, indicating discount rates in our strategic context of about 50 percent, much higher than the ones typically observed in individual decision contexts. Finally, when both costs and benefits are delayed to the same extent, contribution levels do not change, indicating that cooperation is time-consistent.
Keywords: H41; D63; C92; 330; Public goods; cooperation; discounting; time preferences; delay